Reducing Plagiarism among the Students’ Essays in the Light of Ethical Perspective - Halim Wiryadinata; Jootje Musa Pankey (Sekolah Tinggi Teologi Paulus Medan, Sumatra Utara, 2020)
An essay is one of the assignments that have been given by the lecturers to the students involved in the subject. However, the given essay is done by the undergraduate students of Sekolah Tinggi Teologi Pelita Bangsa contained as the plagiarism work, which is analyzed by the Turnitin tool. Plagiarism is committed among 27% - 35% as found through the Turnitin tool and it seems to increase gradually every semester. This “criminal work” needs to be minimalized, where the standard of Sekolah Tinggi Teologi Pelita Bangsa is being set up and must be met by the Word of God which says, “Do not steal.” If the problem is not sorted out then the increasing number of plagiarisms threatens the academic standard of academicians at ST Pelita Bangsa. Therefore, this research must be conducted through careful analysis via qualitative methodology by interviewing the students and the lecturers. The finding is that students don't know how to write an essay due to the lack of practicing from the beginning of the new academic year and the limited number of books at the library is the motive for the students doing it. The latter recommendation must be done to prevent the increase of plagiarism.